2008
DOI: 10.1101/lm.1078508
|View full text |Cite
|
Sign up to set email alerts
|

Immediate extinction causes a less durable loss of performance than delayed extinction following either fear or appetitive conditioning

Abstract: Five experiments with rat subjects compared the effects of immediate and delayed extinction on the durability of extinction learning. Three experiments examined extinction of fear conditioning (using the conditioned emotional response method), and two experiments examined extinction of appetitive conditioning (using the food-cup entry method). In all experiments, conditioning and extinction were accomplished in single sessions, and retention testing took place 24 h after extinction. In both fear and appetitive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
66
3
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(84 citation statements)
references
References 72 publications
14
66
3
1
Order By: Relevance
“…Contextual fear memory is known to undergo major reorganization between recent and remote stages (Frankland et al, 2004). For instance, remote contextual memories are stored in distributed cortical networks (Woods and Bouton, 2008). It remains to be shown whether auditorycured fear memory undergoes similar changes and whether these changes are the cause for the less efficient within-session extinction at late time points after conditioning.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Contextual fear memory is known to undergo major reorganization between recent and remote stages (Frankland et al, 2004). For instance, remote contextual memories are stored in distributed cortical networks (Woods and Bouton, 2008). It remains to be shown whether auditorycured fear memory undergoes similar changes and whether these changes are the cause for the less efficient within-session extinction at late time points after conditioning.…”
Section: Discussionmentioning
confidence: 99%
“…Other than for contextual fear memory (Woods and Bouton, 2008), little is known about the dependency of fear extinction on the age of cued fear memories. The only exceptions are studies investigating consequences of extinction training initiated early after conditioning (e.g., Myers et al, 2006;Kim and Richardson, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…An initial study by Myers et al (2006) using fearpotentiated startle reported that extinction within a few minutes after acquisition (immediate extinction) caused a more durable suppression of the conditioned response than did extinction 24 h after acquisition. However, subsequent studies using aversive (Maren and Chang 2006;Woods and Bouton 2008;Chang and Maren 2009;Archbold et al 2010;Stafford et al 2013) and appetitive procedures (Rescorla 2004;Woods and Bouton 2008) in rodents as well as humans (Norrholm et al 2008;Schiller et al 2008) failed to observe superiority of immediate extinction. Indeed, in a number of studies immediate extinction was less effective than delayed extinction at suppressing the CR (Rescorla 2004;Maren and Chang 2006;Woods and Bouton 2008;Chang and Maren 2009;Stafford et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Most of the previous studies conditioned subjects to discrete auditory or visual cues and did not examine extinction of context fear directly (Cain et al 2005;Alvarez et al 2007;Norrholm et al 2008;Schiller et al 2008;Woods and Bouton 2008;Huff et al 2009;Johnson et al 2010;Kim et al 2010;MacPherson et al 2013). It is well established that cued and context fear conditioning recruit distinct neural mechanisms (Kim and Fanselow 1992;Phillips and LeDoux 1992;Maren et al 1997), raising the possibility that cued and context conditioning are differentially sensitive to immediate extinction.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with fear conditioning to a discrete cue identified several factors that affect the resistance of extinction to recovery. These include the interval between conditioning and extinction (Myers et al 2006;Woods and Bouton 2008;Huff et al 2009; but see Alvarez et al 2007;Schiller et al 2008;Archbold et al 2010), the interval between extinction and test (Bouton 1993(Bouton , 2004Quirk 2002), the level of fear behavior at extinction (Maren and Chang 2006), and the number and pattern of nonreinforced trails (Cain et al 2003;Urcelay et al 2009). These factors would be expected to interact with each other such that the precise experimental conditions used by independent laboratories would differentially reveal recovery of the cued fear responses.…”
Section: Discussionmentioning
confidence: 99%